Late Brachial Artery Thrombosis after Supracondylar Humeral Fracture at 5 Years Old Boy - Tomaszewski, Ryszard; Wozowicz, Artur; Wysocka, Paulina (International Journal of Orthopedics and Rehabilitation, 2015)
Supracondylar fractures in children is a well known problem, but late neuro-vascular complications related to the fractures of the distal part of the humerus in children are rare. There has been presented the case of a patient after a supracondylar fracture with slow brachial artery thrombosis.